How do government subsidies and consumers' low-carbon preference promote new energy vehicle diffusion? A tripartite evolutionary game based on energy vehicle manufacturers, the government and consumers. Issue 3 (March 2023) - Shi, Zhiying; Cheng, Jingwei
Abstract: At present, the diffusion and trading volume of new energy vehicles (NEVs) account for only a small part of the automobile market. How to effectively promote the production of energy vehicle manufacturers and the purchase of consumers for NEVs has become a key and urgent problem to be solved. Our research builds an evolutionary game model including government, consumers and energy vehicle manufacturers from the perspective of supply chain research, and discusses the participants' evolutionary stability strategy and portfolio stability strategy. In addition, the method of simulated moments is used to assign values to the model data, and MATLAB software is used for simulation verification and analysis. Through analysis, it is found that: (1) The government, energy vehicle manufacturers and consumers influence each other in their strategic choices, but to different degrees. (2) The difference of government subsidy objects will not affect the evolution direction and result of the diffusion game model of NEVs, but will affect the stable speed of strategic behavior and the change direction of strategic choice of consumers and energy vehicle manufacturers. And in the case of moderate subsidies, subsidies to energy vehicle manufacturers can promote the NEV diffusion. (3) Improving the environmental friendliness of NEVs and improving consumers' low-carbon preference for NEVs have about the same effect on the replicative power system. And compared with other key factors, they are the most favorable way to promote NEVs diffusion. At last, suggestions are put forward according to the research conclusions.